How 3D Interaction Metaphors Affect User Experience in Collaborative Virtual Environment - Hamid Hrimech; Leila Alem; Frederic Merienne (Advances in Human-Computer Interaction)
In this paper we presents the results of our experimental study which aims to understand the impact of three interaction 3D metaphors (ray casting, GoGo, and virtual hand) on the user experience in a semi-immersive collaborative virtual environment (the Braccetto System). For each session, participants are grouped in twos to reconstruct a puzzle by an assemblage of cubes. The puzzle to reconstruct corresponds to a gradient of colors. We found that there is a significant difference in the user experience by changing the interaction metaphor on the copresence, awareness, involvement, collaborative effort, satisfaction usability, and preference. These findings provide a basis for designing 3D navigation techniques in a CVE.